A Multi-Criteria Decision-Making Approach for Woven Fabric Selection and Grading for Ladies Summer Apparel. Issue 10 (3rd October 2021) - Iftikhar, Fatima; Ali, Zulfiqar; Hussain, Tanveer; Nazir, Ahsan; Adolphe, Dominique C.
ABSTRACT: In the garment industry, selection of the most appropriate fabric for apparel manufacturing plays a vital role in customer satisfaction. Identification of the best fabric from a set of available options in the presence of conflicting selection criteria is often a quite challenging multi-criteria decision-making problem. In this study, analytic hierarchy process (AHP) and Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) are used to solve fabric selection problem for apparel manufacturing. The AHP identifies relative weights of the selection criteria, whereas the PROMETHEE II method ranks the alternative fabrics based on their net outranking flows. The ranking of cotton fabrics based on multiple decision criteria of different weights is successfully achieved using combined AHP and PROMETHEE approach, which is applicable to selection of textile raw materials at any stage of the value chain. AHP and Visual PROMETHEE approach are integrated to provide a holistic methodology for fabric ranking and selection in the light of multiple selection criteria.